Auroral evidence of radial transport at Jupiter during January 2014. Issue 10 (31st October 2016) - Gray, R. L.; Badman, S. V.; Bonfond, B.; Kimura, T.; Misawa, H.; Nichols, J. D.; Vogt, M. F.; Ray, L. C.
Abstract: We present Jovian auroral observations from the 2014 January Hubble Space Telescope (HST) campaign and investigate the auroral signatures of radial transport in the magnetosphere alongside contemporaneous radio and Hisaki EUV data. HST FUV auroral observations on day 11 show, for the first time, a significantly superrotating polar spot poleward of the main emission on the dawnside. The spot transitions from the polar to main emission region in the presence of a locally broad, bright dawnside main emission feature and two large equatorward emission features. Such a configuration of the main emission region is also unreported to date. We interpret the signatures as part of a sequence of inward radial transport processes. Hot plasma inflows from tail reconnection are thought to flow planetward and could generate the superrotating spot. The main emission feature could be the result of flow shears from prior hot inflows. Equatorward emissions are observed. These are evidence of hot plasma injections in the inner magnetosphere. The images are thought to be part of a prolonged period of reconnection. Radio emissions measured by Wind suggest that hectometric (HOM) and non‐Io decametric (DAM) signatures are associated with the sequence of auroral signatures, which implies a global magnetospheric disturbance. The reconnection and injection interval can continue for several hours. Key Points: On 11 January 2014 Jupiter's UV aurora exhibits a superrotating polar spot: Signature of tail reconnection Concurrent bright, broad main emission results from enhanced flow shears around reconnection inflows Large equatorward emissions are signatures of hot plasma injections from earlier reconnection inflow